A Maqāṣid-Based Framework for Managing Religious Offense: Insights from the Prophetic Sirah - Khairul Azhar Meerangani; Mohammad Fahmi Abdul Hamid; Muaz Mohd Nor; Taufiqurrahman Taufiqurrahman (International Journal of Religious and Interdisciplinary Studies, 2026)
Religious offense has become an increasingly volatile phenomenon in plural societies, often triggering polarized responses that oscillate between unconditional tolerance and uncompromising severity. Within Islamic discourse, the Prophetic model of coexistence is frequently invoked but is often reduced to selective narratives that obscure its contextual ethical logic. This study re-examines al-taʿāyush through a qualitative analysis of Prophetic responses to religious offense across both the Makkan and Madinan periods. The study aims to identify the ethical parameters governing these responses and to formulate a structured framework for analyzing religious offense in plural societies. Using qualitative textual analysis, the research examines a corpus of documented Sirah incidents drawn from classical prophetic biographies and authenticated ḥadīth sources that describe cases of insult, provocation, or hostility toward religion. The narratives were analyzed using thematic coding combined with a maqāṣid-oriented analytical lens. The findings show that Prophetic responses were not uniform but structured by identifiable parameters, including intentionality, public-harm thresholds, authority configuration, consequential assessment (maʾālāt), and balancing maslaḥah–mafsadah. These findings demonstrate that al-taʿāyush functioned as a context-sensitive ethical framework rather than a simplistic ethic of tolerance. The proposed parameterization offers an analytical tool for evaluating contemporary cases of religious offense in the public sphere while maintaining ethical coherence within Islamic normative thought.